Bioethics and vulnerability : a Latin American view - Luna, Florencia (Value inquiry book series., 2006)
"This book presents some of the challenges bioethics in Latin America faces today. It considers them through the lenses of vulnerable populations, those incapable of protecting their own interests, such as the illiterate, women in societies disrespectful of their reproductive rights, and research subjects in contexts where resources are scarce."--Publisher